ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI SAYURAN ORGANIK DI SUPERMARKET KABUPATEN SLEMAN - Sumarliningsih, Efi; Budiarto, Budiarto; Juarini, Juarini (Jurnal Dinamika Sosial Ekonomi, 2017)
This research is intended to (1) analyze the influences of culutural factors, socialclasses, reference groups, families, life style, perception as well as the consumers decision in buying organic vegetables and (2) identify the consumers knowledge about the organic vegetables in the framework of food safety in Supermarkets. The research applied here was a survey method. The survey location waspurposively decided in four supermarkets assumed to sell organic vegetablesunder the trade-mark of TOM (Tani Organik Merapi) Gemilang which has already been certified by SNI 6729-2010 No. : 014/LSPO-007-IDN/0712/2013. The research was conducted in four supermarkets located in Depok Sub-District, Sleman Regency, Mirota Babarsari, Lion Superindo Jalan Kaliurang, Lion Superindo Seturan and Giant Expres Depok. The respondents were taken throught Quota Sampling. The respondents in this research were consumers both buying and not-buying the organic vegetables in Mirota Babarsari, Lion Superindo Jalan Kaliurang, Lion Superindo Seturan, and Giant Expers Depok. There were 120 respondents from the four supermarkets meaning that there wrere 30 respondents from each supermarket. The data were collected through observation, interview an notes taking. The analysis models used in this research were Logistic Regression Analysis and descriptive analysis. The results of this research showed that (1) culture, social classes, families, and attitude significantly influenced the consumers decision to buy organic vegetables mean while the reference groups, perception, and life style did not significantly influence the consumers decision to buy organic vegetables ; (2) however, theconsumers knowledge, concerningthe food safety, of eithet buying or not-buying organic vegetables is quite high.Â Keyword: Decision Making Factor, organic Vegetable, Culture, Consumers knowledge, Food Safety